2015
DOI: 10.1016/j.devcel.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Nerves Regulate Cardiomyocyte Proliferation and Heart Regeneration

Abstract: SUMMARY Some organisms, such as adult zebrafish and newborn mice, have the capacity to regenerate heart tissue following injury. Unraveling the mechanisms of heart regeneration is fundamental to understanding why regeneration fails in adult humans. Numerous studies have revealed that nerves are crucial for organ regeneration, thus we aimed to determine whether nerves guide heart regeneration. Here, we show using transgenic zebrafish that inhibition of cardiac innervation leads to reduction of myocyte prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
230
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(237 citation statements)
references
References 52 publications
6
230
1
Order By: Relevance
“…Recent studies have also spotlighted the underappreciated influence of additional non-myocardial types on injury-induced heart regeneration. A series of experiments examined the role that nerves play after cardiac injury in both zebrafish and mice (Mahmoud et al, 2015). In these studies it was shown that induced cardiac expression of a known inhibitor of innervation in zebrafish leads to reduced cardiomyocyte proliferation after ventricular injury and disrupts regeneration.…”
Section: Participation Of Non-muscle Cell Types In Regenerationmentioning
confidence: 99%
“…Recent studies have also spotlighted the underappreciated influence of additional non-myocardial types on injury-induced heart regeneration. A series of experiments examined the role that nerves play after cardiac injury in both zebrafish and mice (Mahmoud et al, 2015). In these studies it was shown that induced cardiac expression of a known inhibitor of innervation in zebrafish leads to reduced cardiomyocyte proliferation after ventricular injury and disrupts regeneration.…”
Section: Participation Of Non-muscle Cell Types In Regenerationmentioning
confidence: 99%
“…Interestingly, there was no increase in binucleation but rather an increase of nuclear ploidy with age. The recalcitrance of adult cardiomyocytes to go through cytokinesis may have multiple causes, such as physical hindrance by sarcomeres, 26 lack of hormonal or neural signals controlling postnatal growth, 5,27 and changes in epigenetic pathways. 28 As the body of evidence supporting cardiomyocytes as the most important cellular source of heart regeneration grows, it has become critically important to unlock the mechanisms that control mitosis and cytokinesis of adult cardiomyocytes and identify strategies to enhance cardiomyocyte regeneration.…”
Section: Proliferation Potential Of Cardiomyocytesmentioning
confidence: 99%
“…However, their function in cardiac regeneration was not determined until recently (Kumar and Brockes, 2012). In this frontier, Mahmoud et al (2015) reported that pharmacological inhibition of the cholinergic nerve formation in zebrafish and newborn mice reduced cardiomyocyte proliferation following injury, thus suggesting that innervation is crucial for heart regeneration (Mahmoud et al, 2015). Moreover, the mechanical inhibition of innervation (left vagotomy) decreases the cardiac regenerative response in newborn mice that could be rescued by recombinant neuregulin 1 (NRG1) and nerve growth factor (NGF) administration.…”
Section: Kip2mentioning
confidence: 99%
“…Moreover, the mechanical inhibition of innervation (left vagotomy) decreases the cardiac regenerative response in newborn mice that could be rescued by recombinant neuregulin 1 (NRG1) and nerve growth factor (NGF) administration. In addition, they reported that the immune response and inflammatory associated genes are downregulated following denervation, which shows that denervation impairs heart regeneration through downregulating the immune response mechanism (Mahmoud et al, 2015).…”
Section: Kip2mentioning
confidence: 99%